Evaluation results and psychosocial profile of a rehabilitation program for people with drug abuse. - Valero, Luis; Ortiz-Tallo, Margarita; Parra-García, María del Mar; Jiménez-Guerra, Marta (Anales de Psicología / Annals of Psychology, 2013)
This research group carried out an evaluation of data collected over the last 3 years, from the drug addiction rehabilitation program Pro- yecto Hombre Málaga. The sample consisted of 96 participants from 18 to 56 years old (M=31.31, DT=14.20), i.e., 83.3% male and 16.7% female. The rate of success, those who finished the therapeutic program successfully, was 22.9%. The various psychosocial characteristics were studied, and related to the likelihood of therapeutic success, dropouts and relapse back into addiction. Details of the results and statistical analysis of the personal characteristics, family and consumer products are shown. The principal factors related to dropouts were found to be: poly-drug use, physical and emotional abuse and especially, frequent family conflicts. Therapeutic guidelines are suggested which improve the overall results and help resolve family conflicts that could be an important factor for relapse and for dropping out of the program.